Determination of minimum serum concentration to develop scaffold free micro-tissue - Karaman, Ozan; Yaralı, Ziyşan Buse (The European Research Journal, 2018)
Objective. Formation of three-dimensional (3D) micro-tissues without scaffolds are widely used not only to define in vivo tissue formation mechanisms but also the development of different tissue-specific drugs. However, depending on high serum and growth factor concentrations, it would be hard to identify major effective biological cues on micro-tissue formation. The aim of the study is to determine the effect of different serum concentrations on Human Umbilicial Vein Endothelial Cells (HUVECs) micro-tissue formation.Methods. Micro-tissue of HUVEC line was formed by using 3D petri dish technique with medium containing 0%, 1%, 5% and 10% fetal bovine serum (FBS). On the 7th day after micro-tissue formation, live/dead cells analysis was conducted. Micrograph taken on days 1, 3, 5 and 7th of micro-tissue formation were determined by image analysis with ImageJ.Results. Sizes of micro-tissue formed with 0% FBS on day 1 and 3 determined as 277 ± 12 µm and 279 ± 20 µm, respectively; however, especially on day 7 micro-tissue size significantly decreased to 229 ± 6 µm. When live/dead analysis results were examined, high cell viability was observed in 5% and 10% FBS concentration. Although micro-tissue like structures were observed in 0% and 1% FBS concentrations dead cell ratio considerably increased compared to 5% and 10% FBS concentration. Conclusions. It has been determined that 0% and 1% serum are appropriate for determining the efficacy of biomimetic peptides and different extracellular matrix proteins on micro-tissue formation parameters of HUVEC. High cell viability in micro-tissues was observed with 5% and 10% serum concentrations.